Design of radiation pattern reconfigurable microstrip antenna arrays / Nurfarahin Afiqah Zaiki - Zaiki, Nurfarahin Afiqah (2013)
This paper reports the design of radiation pattern reconfigurable microstrip patch antenna arrays. The design applies the quarter-wave transformer concept in producing a feed line that divides the power equally for an eight element linear array of rectangular microstrip patch. The objective of this project is to compare the radiation pattern and gain with increasing array element. The design uses two switches and operates at the frequency of 5.8 GHz for wireless applications. This paper focuses on the comparison of beamwidths obtained from arrays made of four and eight elements. The antennas demonstrate reconfigrability by producing narrow (concave) or wide (convex) beams. The performance of the radiation pattern reconfigurable microstrip patch antenna array was examined based on the radiation pattern characteristics. Two different beam patterns were produced in accordance to the number of elements used. The configurability was achieved by employing a 0.5 mm wide microstrip slit to replace the switch.